ChemInform Abstract: The Use of a Mitsunobu Reagent for the Formation of Heterocycles: A Simple Method for the Preparation of 3‐Alkyl‐5‐aryl‐1, 3, 4‐oxadiazol‐2(3H)‐ones from Carboxylic Acids. Issue 48 (2nd December 2014) - Sugimoto, Osamu; Arakaki, Tomoyo; Kamio, Hiroka; Tanji, Ken‐ichi
Abstract The reaction proceeds smoothly when Mitsunobu reagents with smaller alkyl groups are used.